PALEOMAGNETISM AND THE TECTONIC EVOLUTION OF THE IONIAN ZONE, NORTHWESTERN GREECE - Broadley L.; Platzman E.; Platt J.; Papanikolaou M.; Matthews S. (My University, 2006)
The Ionian zone is a classic thin-skinned linear fold and thrust belt forming a part of the external Hellenides, in westernmost Greece. The region has been a focus of intensive paleomagnetic investigation since the early 1980s, and it is now generally believed to have undergone a multiphase clockwise vertical-axis rotation of 40°-60° since the Miocene, although the timings are disputed, and spatial variations within this trend have been largely ignored thus far. We present data from thirty new paleomagnetic sites and a reappraisal of previous results from the Ionian zone in an attempt to construct a unified model for the tectonic evolution of the Ionian zone. We find that the clockwise rotations may be due, at least partially, to rotation during thrust sheet emplacement, with evidence of a forelandward decrease in rotation. However, superimposed on this pattern of thin-skinned rotations we observe post-Pliocene rotations that affect multiple thrust sheets in a consistent manner. These are interpreted to result from regional tectonics associated with, for example, the Kefallonia fault zone at the western termination of the Hellenic arc and from deformation in the transition zone between Anatolian westward extrusion and southern Aegean extension. Overall, the result is a pattern of thin-skinned, westward-decreasing clockwise rotations distorted by superimposed thick-skinned rotations resulting from the complex interplay of plate motions in the eastern Mediterranean.
Keywords: GREECE; IONIAN ZONE; PALEOMAGNETISM; TECTONICS; VERTICAL AXIS ROTATION; Pliocene; Miocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен